2015
DOI: 10.1371/journal.pone.0129338
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Stability in Postmortem FFPE Tissues: Quantitative Analysis Using Autoptic Samples from Acute Myocardial Infarction Patients

Abstract: MicroRNAs (miRNAs) are very short (18–24 nucleotides) nucleic acids that are expressed in a number of biological tissues and have been shown to be more resistant to extreme temperatures and pH compared to longer RNA molecules, like mRNAs. As miRNAs contribute to diverse biological process and respond to various kinds of cellular stress, their utility as diagnostic biomarkers and/or therapeutic targets has recently been explored. Here, we have evaluated the usefulness of miRNA quantification during postmortem e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 43 publications
4
44
2
Order By: Relevance
“…In contrast, the small nucleolar and mRNAs were closely correlated in only freeze-thawed and FFPE specimens, highlighting the propensity for fixation and tissue damage to degrade most nucleic acids [61]. One study limitation is that miRNAs were extracted with different methods for frozen and FFPE tissue, as is the case for other studies [60,61,69]. A separate study demonstrated similar findings for two miRNAs in snap frozen and FFPE specimens from multiple mouse and human tissue specimens [68].…”
Section: Routine Ffpe Specimens Vs Frozen Specimensmentioning
confidence: 91%
See 4 more Smart Citations
“…In contrast, the small nucleolar and mRNAs were closely correlated in only freeze-thawed and FFPE specimens, highlighting the propensity for fixation and tissue damage to degrade most nucleic acids [61]. One study limitation is that miRNAs were extracted with different methods for frozen and FFPE tissue, as is the case for other studies [60,61,69]. A separate study demonstrated similar findings for two miRNAs in snap frozen and FFPE specimens from multiple mouse and human tissue specimens [68].…”
Section: Routine Ffpe Specimens Vs Frozen Specimensmentioning
confidence: 91%
“…First, miRNAs are robust, and, when compared to other nucleic acids, better tolerate both direct and tissue insults. For example, various markers of total RNA integrity including electropherograms [55,56,[59][60][61] and RNA integrity number (RIN) [57,61] do not correlate with miRNA integrity, which consistently remains detectable despite overall specimen decay. Second, while standardized pre-analytical conditions for tissue samples are ideal, it is not always practical and variation in the above variables should be recorded and analyzed as potential confounders.…”
Section: Pre-analytical Variables For Tissue-based Analysis Of Mirnasmentioning
confidence: 99%
See 3 more Smart Citations